Fatigue behavior of 17-4 PH parts produced by Material Extrusion Additive Manufacturing: A study on thickness and notch effects (Fracture and Structural Integrity, 2026)
17-4 PH specimens were produced using the three-step process referred to as Material Extrusion Additive Manufacturing (MEAM), which involves printing components with a composite feedstock of metal powder and polymers, followed by a debinding process to remove the polymer, and a final sintering process to obtain the finished metallic part. The process enables the production of metallic components at a limited cost and with reduced safety issues in comparison to other additive manufacturing processes. With the goal of exploring and evaluating the fatigue properties of 17-4 PH MEAM specimens, two experimental campaigns were designed. The first with the objective of assessing the effect of thickness on the fatigue performance of smooth specimens, and the second aimed to investigate the notch effect on the fatigue limit of different notched specimens. The smooth specimens were fabricated with a thickness ranging between 1 and 5 mm, while the notched specimens were fabricated with a thickness of 3 mm, with 90° and 30° notch opening angles. The mechanical properties of the smooth series proved not to be affected by the thickness, neither for quasi-static nor cyclic response. On the contrary, the fatigue behavior of the notched specimens was significantly influenced by the presence of the notch, with sharper notches exhibiting a more negative impact. Moreover, the findings revealed that the fabrication of specimens characterized with thin sections, small geometrical features, and acute notches presented significant challenges, posing a severe issue regarding the practical applicability of MEAM for real-life complex geometries.
Keywords: Additive; stainless steel; fatigue; thickness; notch